An active composite membrane loaded with EGCG@CD-MOF for fresh-keeping and deodorization of aquatic products and a preparation method thereof

CN122898043APending Publication Date: 2026-10-13ZHEJIANG GONGSHANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610714330.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-22
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]本发明是为了克服现有技术中的鲣鱼、大目金枪鱼、蓝鳍金枪鱼、三文鱼等水产品冷链贮藏过程中的品质劣变、腥味突出,水产品保鲜和去腥不足的缺陷,提供了一种用于水产品保鲜去腥的负载EGCG@CD-MOF活性复合膜及其制备方法

Benefits of technology

(1)三重功能协同:本发明首次将EGCG@CD-MOF引入SA-PVA活性包装膜体系,并专门用于金枪鱼等水产品,实现了EGCG对水产品脂质氧化的源头抑制、CD-MOF对腥味分子的原位物理吸附以及SA-PVA基材的结构保鲜功能的三重协同。经实验验证,在4 ℃冷藏条件下,本发明的活性复合膜处理组的鲣鱼中己醛(关键腥味标志物)含量较空白对照下降25%以上,1-辛烯-3-醇含量下降26%~27%;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898043A_ABST
    Figure CN122898043A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of food packaging materials, and particularly relates to a loaded EGCG@CD-MOF active composite film for fresh-keeping and deodorization of aquatic products and a preparation method thereof. The present application introduces EGCG@CD-MOF into the SA-PVA active packaging film system for the first time, and is specially used for tuna and other aquatic products, realizing the triple synergy of source inhibition of lipid oxidation of aquatic products by EGCG, in-situ physical adsorption of CD-MOF on odor molecules and the structure fresh-keeping function of the SA-PVA substrate. It is verified by experiments that under the cold storage condition at 4 DEG C, the content of hexanal (a key odor marker) in the tuna of the active composite film treatment group of the present application is reduced by more than 25% compared with the blank control, and the content of 1-octen-3-ol is reduced by 26% to 27%. The active composite film material of the present application shows strong inhibitory activity (bacteriostatic rate close to 100%) on gram-positive bacteria such as Staphylococcus aureus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of food packaging materials technology, specifically relating to an EGCG@CD-MOF loaded active composite film for preserving and removing the fishy smell of aquatic products and its preparation method. Background Technology

[0002] High-end seafood products such as tuna (including skipjack tuna, bigeye tuna, bluefin tuna, and yellowfin tuna) and salmon are rich in polyunsaturated fatty acids (PUFAs) and high-quality protein, making them an important part of the global high-end food market. However, these seafood products are highly susceptible to lipid oxidation and protein degradation during cold chain storage, producing aldehydes (such as hexanal, heptanal, and nonanal) and alcohols (such as 1-octen-3-ol) that produce fishy odors. This is accompanied by microbial spoilage, leading to deterioration in product quality and a significantly shortened shelf life, severely limiting their high-end market value. Taking bigeye tuna (Thunnus obesus) as an example, the high content of unsaturated fatty acids in its muscle is particularly prone to oxidative degradation during refrigeration. Consumers are far more sensitive to fishy odors than to ordinary seafood, and existing preservation methods still have significant shortcomings in controlling fishy odors and maintaining quality.

[0003] Epigallocatechin gallate (EGCG) is the main active component of tea polyphenols, possessing excellent antioxidant properties and broad-spectrum antibacterial activity. Existing research indicates that EGCG can achieve highly efficient deodorization of aquatic products through a dual pathway of inhibiting lipoxygenase (LOX) activity and competing for myofibrillar protein binding sites. However, the phenolic hydroxyl structure of EGCG itself is highly susceptible to oxidative degradation under light, high temperature, and neutral or alkaline conditions, leading to a significant decrease in biological activity and limiting its direct application in the field of aquatic product preservation.

[0004] Cyclodextrin-based metal-organic frameworks (CD-MOFs) are three-dimensional porous materials formed by the self-assembly of cyclodextrin and alkali metal ions through coordination bonds. They combine the host-guest inclusion capabilities of cyclodextrin with the high porosity of MOFs. Studies have shown that CD-MOFs can effectively encapsulate bioactive components such as EGCG, improving their stability in adverse environments and imparting sustained-release properties. However, there are few reports on high-end active preservation packaging films for aquatic products based on CD-MOFs in the current technology, especially regarding the integration of CD-MOF-loaded EGCG composite systems into biodegradable polymer-based films to simultaneously achieve the triple functions of physical preservation, chemical anti-oxidation, and odor adsorption. A systematic technical solution is still lacking in this area.

[0005] Sodium alginate (SA) and polyvinyl alcohol (PVA) are biodegradable packaging substrates, but pure SA films have poor mechanical properties and insufficient water resistance, while pure PVA films lack antioxidant and antibacterial activities. Therefore, the combination of these two materials presents a problem of complementary mechanical properties but insufficient functionality. Existing literature has reported on sodium alginate-polyvinyl alcohol (SA-PVA) composite films, but there is no evidence of introducing EGCG@CD-MOF active materials into the SA-PVA system to construct an active biodegradable composite film with three functions: slow-release antioxidant, in-situ odor adsorption, and mechanical enhancement, specifically for the preservation and deodorization of high-end aquatic products such as tuna. Summary of the Invention

[0006] This invention aims to overcome the shortcomings of existing technologies in the cold chain storage of aquatic products such as skipjack tuna, bigeye tuna, bluefin tuna, and salmon, which result in quality deterioration, prominent fishy smell, and insufficient preservation and deodorization. It provides an EGCG@CD-MOF loaded active composite membrane for the preservation and deodorization of aquatic products and its preparation method.

[0007] To achieve the above-mentioned objectives, the present invention is implemented through the following technical solution: An EGCG@CD-MOF-loaded active composite membrane for preserving and removing the odor of aquatic products, the active composite membrane comprising sodium alginate, polyvinyl alcohol and EGCG@CD-MOF complex; the EGCG@CD-MOF complex is prepared by loading epigallocatechin gallate (EGCG) into a β-cyclodextrin-based metal-organic framework (β-CD-MOF).

[0008] This invention introduces a β-cyclodextrin-based metal-organic framework (β-CD-MOF) as a carrier, utilizing its regular nanoporous structure to confine and encapsulate EGCG molecules. This fundamentally alters the form of EGCG, transforming it from a free state to a caged, stable state, effectively blocking the attack pathways of external environmental factors on the active groups of EGCG and solving the problem of rapid inactivation of EGCG during storage and use. Simultaneously, β-CD-MOF itself possesses excellent host-guest recognition capabilities and a large specific surface area, enabling it to actively capture and lock in typical volatile substances with fishy odors, such as trimethylamine and pentanal, released from aquatic products. Furthermore, this invention utilizes the abundant hydrogen bond network and interpenetrating entanglement structure between the molecules of sodium alginate and polyvinyl alcohol in a compound system to construct a dense physical barrier. This not only significantly enhances the mechanical strength and flexibility of the active composite membrane, but more importantly, it achieves slow release regulation of the active ingredients in the EGCG@CD-MOF complex by controlling the free volume of polymer segments, avoiding the burst release phenomenon of active substances.

[0009] Preferably, the mass ratio of sodium alginate to polyvinyl alcohol is 1:0.5~2.

[0010] As a further preferred embodiment, the mass ratio of sodium alginate to polyvinyl alcohol is 1:1.

[0011] Preferably, the active composite membrane also contains glycerol.

[0012] The preparation method of the EGCG@CD-MOF loaded active composite membrane for preserving and removing odor from aquatic products, as described above, includes the following steps: S1: β-Cyclodextrin was dissolved in water with a strong base and crystallized by methanol vapor diffusion to obtain β-CD-MOF crystals; S2: Epigallocatechin gallate (EGCG) and the β-CD-MOF crystals obtained in step S1 are mixed in an organic solvent, stirred in the dark, centrifuged, washed and dried to obtain the EGCG@CD-MOF complex; S3: Dissolve sodium alginate and polyvinyl alcohol in water, heat and stir until completely dissolved, and cool to obtain sodium alginate-polyvinyl alcohol (SA-PVA) film-forming solution; S4: Add the EGCG@CD-MOF complex and glycerol obtained in step S2 to the sodium alginate-polyvinyl alcohol film-forming solution obtained in step S3, stir evenly, degas, cast into a film by casting method, and dry to obtain the active composite film (SA-PVA-EGCG@CD-MOF).

[0013] Preferably, the mass ratio of epigallocatechin gallate to β-CD-MOF crystals added in step S2 is 1:0.5~3.

[0014] As a further preferred option, the mass ratio of epigallocatechin gallate to β-CD-MOF crystals added in step S2 is 1:2.

[0015] Preferably, the ratio of the EGCG@CD-MOF complex added in step S4 to the sodium alginate-polyvinyl alcohol film-forming solution is 0.3~2.0:1 mg / mL.

[0016] As a further preferred option, the ratio of the EGCG@CD-MOF complex added in step S4 to the sodium alginate-polyvinyl alcohol film-forming solution is 0.7~0.9:1 mg / mL.

[0017] Preferably, the glycerol added in step S4 accounts for 0.5 to 2.0% of the volume of the sodium alginate-polyvinyl alcohol film-forming solution.

[0018] As a further preferred option, the glycerol added in step S4 accounts for 1.0% of the volume of the sodium alginate-polyvinyl alcohol film-forming solution.

[0019] Preferably, in step S1, the diffusion temperature of the methanol vapor diffusion process is 40~60 ℃ and the diffusion time is 8~24 h; the crystallization temperature is 20~30 ℃ and the crystallization time is 12~48 h.

[0020] Preferably, the organic solvent in step S2 is methanol; and the stirring time in the dark is 2-8 h.

[0021] As a further preferred option, the stirring time in step S2 in the dark is 5 h.

[0022] Preferably, the heating temperature for heating and stirring in step S3 is 50~80 ℃.

[0023] Preferably, in step S4, ultrasonic treatment for 10-60 min is used for degassing, the drying temperature is 25-40 ℃, and the drying time is 12-48 h.

[0024] The above describes the application of an EGCG@CD-MOF-loaded active composite membrane for preserving and removing the odor from aquatic products.

[0025] The above-mentioned application of an EGCG@CD-MOF-loaded active composite film for preserving and removing the odor of aquatic products in the cold chain storage of fresh-cut or whole aquatic products.

[0026] Preferably, the aquatic products include one or more of skipjack tuna (Katsuwonus pelamis), bigeye tuna (Thunnus obesus), bluefin tuna (Thunnus thynnus), yellowfin tuna (Thunnus albacares), and Atlantic salmon (Salmo salar).

[0027] This invention has a particularly significant synergistic effect on preserving freshness and removing fishy odor from bigeye tuna; it also has excellent applicability to high-end tuna varieties such as bluefin tuna and yellowfin tuna.

[0028] Preferably, the application includes preserving freshness by inhibiting lipid oxidation and protein degradation of aquatic products, and removing fishy odors by adsorbing and removing aldehydes and alcohols that cause fishy smells.

[0029] Preferably, the active composite membrane is used to encapsulate the muscle tissue of aquatic products and refrigerate them at -4 to 4 ℃.

[0030] Therefore, the present invention has the following beneficial effects: (1) Triple Function Synergy: This invention introduces EGCG@CD-MOF into the SA-PVA active packaging film system for the first time, and specifically for aquatic products such as tuna. It achieves a triple synergy of EGCG inhibiting lipid oxidation in aquatic products, CD-MOF physically adsorbing fishy odor molecules in situ, and the structural preservation function of the SA-PVA substrate. Experimental verification shows that under refrigeration conditions of 4 ℃, the content of hexanal (a key fishy odor marker) in the skipjack tuna treated with the active composite film of this invention decreased by more than 25% compared with the blank control, and the content of 1-octen-3-ol decreased by 26%~27%. (2) Stabilization and sustained release of active EGCG: EGCG was stably encapsulated within the CD-MOF framework through host-guest encapsulation. The hierarchical porous structure of CD-MOF provided a physical microenvironment that isolated EGCG from oxygen and light interference. TGA results showed that the thermal degradation temperature of EGCG in EGCG@CD-MOF was delayed, indicating that its thermal stability was effectively improved. The strong adsorption capacity and hierarchical pores of CD-MOF regulated the release rate of EGCG in the tuna cold chain environment, achieving sustained activity protection for up to 7 days, overcoming the inherent defects of EGCG being easily oxidized and degraded, and having rapid efficacy decay during processing and storage. (3) Superior mechanical properties: The addition of EGCG@CD-MOF increases the tensile strength of the active composite film from 15 MPa to about 20 MPa, enhancing the rigidity of the film without significantly sacrificing its fracture toughness, enabling it to withstand the mechanical load environment in cold chain packaging. The three-dimensional porous structure of CD-MOF and the strong coordination bonds between metal ions and cyclodextrin provide the film with additional high structural stability and mechanical strength; (4) Broad-spectrum antibacterial activity: The active composite membrane material of the present invention exhibits extremely strong inhibitory activity against Gram-positive bacteria such as Staphylococcus aureus (antibacterial rate close to 100%). Verification by 16S rRNA high-throughput sequencing showed that the relative abundance of core putrefactive bacteria such as Pseudomonas spp. on the surface of skipjack tuna muscle was significantly reduced in the active composite membrane-treated group, while the abundance of non-putrefactive bacteria such as Firmicutes increased, demonstrating higher microbial community diversity and stability, effectively reversing the imbalance of microbial community homogeneity during cold storage. (5) Environmental friendliness and food safety: SA and PVA are both biodegradable polymers, and CD-MOF is composed of edible β-cyclodextrin (β-CD) and food-grade potassium ions (K). + The material system comprises EGCG, a natural plant extract, and exhibits significant advantages in environmental friendliness and food safety, aligning with the development direction of green packaging. The preparation process of this invention employs a conventional solution film-forming method, requiring no expensive equipment or extreme reaction conditions, and possesses excellent potential for industrial-scale expansion. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the preparation process of β-CD-MOF and EGCG@CD-MOF in Example 1.

[0032] Figure 2 Fourier transform infrared spectra, X-ray diffraction patterns, differential scanning calorimetry (DSC) curves, and thermogravimetric analysis (TGA) curves for β-CD, CD-MOF, EGCG, and EGCG@CD-MOF. Figure 2 In the figure, A represents the Fourier transform infrared spectrum of β-CD, CD-MOF, EGCG, and EGCG@CD-MOF; Figure 2 B in the diagram represents the X-ray diffraction pattern of β-CD, CD-MOF, EGCG, and EGCG@CD-MOF. Figure 2 C in the figure represents the differential scanning calorimetry curves of β-CD, CD-MOF, EGCG, and EGCG@CD-MOF. Figure 2 D in the figure represents the thermogravimetric analysis curves of β-CD, CD-MOF, EGCG, and EGCG@CD-MOF.

[0033] Figure 3 Density functional theory (DFT) optimization structure and independent gradient model (IGMH) isosurface plot of CD-MOF loaded with EGCG. Figure 3 In the diagram, A represents the density functional theory (DFT) optimized structure of CD-MOF loaded with EGCG; Figure 3 B in the figure is the contour plot of the independent gradient model (IGMH) of the CD-MOF load EGCG.

[0034] Figure 4 The graph shows the scavenging activity of EGCG@CD-MOF against DPPH and ABTS free radicals, as well as its activity against Staphylococcus aureus and Escherichia coli. Figure 4 In the diagram, A represents the scavenging activity of EGCG@CD-MOF against DPPH free radicals. Figure 4 B in the figure represents the scavenging activity of EGCG@CD-MOF against ABTS free radicals. Figure 4 The C in the figure represents the activity of EGCG@CD-MOF against Staphylococcus aureus and Escherichia coli.

[0035] Figure 5 The microstructure of the SA-PVA-EGCG@CD-MOF active composite film includes its surface microstructure, cross-sectional microstructure, Fourier transform infrared spectrum, X-ray diffraction pattern, and differential scanning calorimetry curve. Figure 5 In the figure, A represents the surface microstructure of the SA-PVA-EGCG@CD-MOF active composite film. Figure 5B in the figure represents the cross-sectional microstructure of the SA-PVA-EGCG@CD-MOF active composite membrane. Figure 5 C in the figure represents the Fourier transform infrared spectrum of the SA-PVA-EGCG@CD-MOF active composite film. Figure 5 D in the figure represents the X-ray diffraction pattern of the SA-PVA-EGCG@CD-MOF active composite film. Figure 5 E in the figure represents the differential scanning calorimetry curve of the SA-PVA-EGCG@CD-MOF active composite membrane.

[0036] Figure 6 The graphs show the water contact angle, water vapor transmission rate, water retention rate, thickness, and tensile properties of the active composite membranes with different EGCG@CD-MOF addition concentrations. Figure 6 In the figure, A represents the water contact angle of the active composite membrane under different EGCG@CD-MOF addition concentrations; Figure 6 B in the figure represents the water vapor transmission rate of the active composite membrane under different EGCG@CD-MOF addition concentrations; Figure 6 C in the figure represents the water holding capacity of the active composite membrane under different EGCG@CD-MOF addition concentrations; Figure 6 D in the figure represents the thickness of the active composite film at different EGCG@CD-MOF addition concentrations; Figure 6 E in the figure represents the tensile properties of the active composite membrane at different EGCG@CD-MOF addition concentrations.

[0037] Figure 7 The graph shows the effects of different treatment groups on the color difference, texture characteristics, pH, TVB-N content, and TBARS content of skipjack tuna after 7 days of refrigeration at 4 ℃. Figure 7 Figure A shows the effect of different treatment groups on the color difference of skipjack tuna after 7 days of refrigeration at 4 ℃; Figure 7 Figure B in the figure shows the effect of different treatment groups on the textural properties of skipjack tuna after 7 days of refrigeration at 4 ℃. Figure 7 C in the figure represents the effect of different treatment groups on pH of skipjack tuna after 7 days of refrigeration at 4 ℃; Figure 7 D in the figure represents the effect of different treatment groups on the TVB-N content of skipjack tuna after 7 days of refrigeration at 4 ℃; Figure 7 E in the figure represents the effect of different treatment groups on the TBARS content of skipjack tuna after 7 days of refrigeration at 4 ℃.

[0038] Figure 8 PCA analysis results and phylum and genus-level microbial community composition of skipjack tuna samples from different treatment groups. Figure 8 Figure A in the figure represents the PCA analysis results of skipjack tuna samples from different treatment groups; Figure 8 B in the figure represents the phylum-level microbial community composition of skipjack tuna samples from different treatment groups; Figure 8In the figure, C represents the genus-level microbial community composition of skipjack tuna samples from different treatment groups.

[0039] Figure 9 This section presents a statistical analysis of the types and quantities of volatile substances in skipjack tuna from different treatment groups, along with scatter plots showing the ROAV values. Figure 9 In the figure, A represents a statistical chart of the types and quantities of volatile substances in skipjack tuna from different treatment groups; Figure 9 B in the figure represents the scatter plot of ROAV values ​​in skipjack tuna from different treatment groups. Detailed Implementation

[0040] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.

[0041] Example 1 This embodiment provides an EGCG@CD-MOF loaded active composite membrane for preserving and removing the fishy smell of aquatic products and its preparation method.

[0042] A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing odors from aquatic products includes the following steps: S1: Preparation of β-cyclodextrin-based metal-organic framework (β-CD-MOF) crystals: Weigh 1.12 g of KOH and 2.84 g of β-cyclodextrin (β-CD), dissolve them in 100 mL of deionized water, homogenize, and filter through a 0.45 μm filter membrane. Transfer the filtrate to a sealed container containing methanol and heat at 50 °C for 12 hours to allow methanol vapor diffusion. Then add methanol and polyethylene glycol to the solution and incubate at 25 °C for 24 hours. Collect the precipitated cyclodextrin-based metal-organic framework (CD-MOF) crystals, wash twice with methanol, soak in dichloromethane for 72 hours, and finally dry at 50 °C for 12 hours to obtain β-CD-MOF crystals.

[0043] S2: Preparation of EGCG@CD-MOF complex: Epigallocatechin gallate (EGCG) and the β-CD-MOF crystals obtained in step S1 were added to methanol at a mass ratio of 1:2 (m / m), and the mixture was gently stirred continuously for 5 hours in the dark. The precipitate was then collected by centrifugation at 5000×g for 10 minutes, washed three times with methanol, and dried under vacuum for 12 hours to obtain the EGCG@CD-MOF complex.

[0044] S3: Preparation of sodium alginate-polyvinyl alcohol (SA-PVA) film-forming solution: Accurately weigh 2.5 g of sodium alginate (SA) and 2.5 g of polyvinyl alcohol (PVA), dissolve them in 200 mL of deionized water, and stir magnetically at 60 ℃ for 2 hours until completely dissolved. Cool to room temperature to obtain sodium alginate-polyvinyl alcohol (SA-PVA) film-forming solution.

[0045] S4: Preparation of active composite membrane (SA-PVA-EGCG@CD-MOF): Add the EGCG@CD-MOF composite obtained in step S2 to the sodium alginate-polyvinyl alcohol (SA-PVA) film-forming solution obtained in step S3 (wherein the ratio of the added EGCG@CD-MOF composite to the SA-PVA film-forming solution is 0.7:1 mg / mL), stir in the dark for 10 minutes, then add 1% (v / v) glycerol by volume of the film-forming solution, stir evenly, and sonicate for 30 minutes to remove air bubbles. Pour the film-forming solution into a mold using the casting method and dry it in a 30 ℃ oven for 24 hours. After drying, an active composite membrane (SA-PVA-EGCG@CD-MOF) is obtained. Place the dried active composite membrane in a constant temperature and humidity chamber at 25 ℃ and 50% relative humidity for equilibration and subsequent testing.

[0046] An EGCG@CD-MOF-loaded active composite membrane for preserving and deodorizing aquatic products was prepared by the method described above. The active composite membrane comprises sodium alginate, polyvinyl alcohol, and an EGCG@CD-MOF complex. The EGCG@CD-MOF complex is prepared by loading epigallocatechin gallate (EGCG) into a β-cyclodextrin-based metal-organic framework (β-CD-MOF). A schematic diagram of the preparation process of β-CD-MOF and EGCG@CD-MOF in this embodiment is shown below. Figure 1 As shown.

[0047] Example 2 The difference between this embodiment and Embodiment 1 is that: A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing odor from aquatic products, wherein the ratio of the EGCG@CD-MOF composite to the SA-PVA film-forming solution added in step S4 is 0.8:1 mg / mL. All other steps are the same as in Example 1.

[0048] Example 3 The difference between this embodiment and Embodiment 1 is that: A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing odor from aquatic products, wherein the ratio of the EGCG@CD-MOF composite to the SA-PVA film-forming solution added in step S4 is 0.9:1 mg / mL. All other steps are the same as in Example 1.

[0049] Example 4 The difference between this embodiment and Embodiment 1 is that: A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and deodorizing aquatic products includes the following steps: In step S1, methanol vapor diffusion is performed by heating at 40 °C for 24 hours; followed by static incubation at 20 °C for 48 hours, ultimately yielding β-CD-MOF crystals. In step S2, EGCG and the β-CD-MOF crystals obtained in step S1 are added to methanol at a mass ratio of 1:0.5 (m / m), and the mixture is gently stirred continuously for 2 hours under light-protected conditions, ultimately yielding the EGCG@CD-MOF composite. In step S3, 2.5 g of sodium alginate (SA) and 1.25 g of polyvinyl alcohol (PVA) are accurately weighed, resulting in an SA-PVA film-forming solution. In step S4, 0.5% (v / v) of glycerol is added to the film-forming solution, and after stirring evenly, the mixture is sonicated for 10 minutes to remove air bubbles. The film-forming solution is then poured into a mold using a casting method and dried in an oven at 25 °C for 48 hours. After final drying, an active composite membrane (SA-PVA-EGCG@CD-MOF) was obtained. Everything else was the same as in Example 1.

[0050] Example 5 The difference between this embodiment and Embodiment 1 is that: A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and deodorizing aquatic products includes the following steps: In step S1, methanol vapor diffusion is performed by heating at 60 °C for 8 hours; followed by static incubation at 30 °C for 12 hours, ultimately yielding β-CD-MOF crystals. In step S2, EGCG and the β-CD-MOF crystals obtained in step S1 are added to methanol at a mass ratio of 1:3 (m / m), and the mixture is gently stirred continuously for 8 hours under light-protected conditions, ultimately yielding the EGCG@CD-MOF composite. In step S3, 2.5 g of sodium alginate (SA) and 5 g of polyvinyl alcohol (PVA) are accurately weighed, resulting in an SA-PVA film-forming solution. In step S4, 2.0% (v / v) of glycerol is added to the film-forming solution, and after stirring evenly, the mixture is sonicated for 60 minutes to remove air bubbles. The film-forming solution is then poured into a mold using a casting method and dried in an oven at 40 °C for 12 hours. After final drying, an active composite membrane (SA-PVA-EGCG@CD-MOF) was obtained. Everything else was the same as in Example 1.

[0051] Comparative Example 1 The difference between this comparative example and Example 1 is as follows: This comparative example provides a sodium alginate-polyvinyl alcohol (SA-PVA) based film for preserving aquatic products and its preparation method.

[0052] A method for preparing a sodium alginate-polyvinyl alcohol (SA-PVA) based film for preserving aquatic products, wherein steps S1 and S2 are omitted, steps S3 and S4 are retained, and the EGCG@CD-MOF composite is not added in step S4. The final product is a sodium alginate-polyvinyl alcohol (SA-PVA) based film. Everything else is the same as in Example 1.

[0053] [Comprehensive Performance Testing and Analysis] 1. Physical property characterization of β-CD, CD-MOF, EGCG and EGCG@CD-MOF complex The EGCG@CD-MOF complex was prepared according to the method in Example 1. Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) were performed on β-CD, CD-MOF, EGCG, and the prepared EGCG@CD-MOF complex, respectively.

[0054] The Fourier transform infrared spectroscopy (FT-IR) test method is as follows: The dried sample was mixed with potassium bromide at a ratio of 1:50 (m / m), ground, and then made into a circular thin film. The scanning range of the infrared spectrometer was 4000~400 cm⁻¹. -1 .

[0055] The X-ray diffraction (XRD) testing method is as follows: The diffraction angle 2θ of the scanning area is 3°~90°, and the scanning speed is 2° / min.

[0056] The differential scanning calorimetry (DSC) test method is as follows: A certain amount of sample powder was sealed in an aluminum crucible. The test temperature range was 30~260 ℃, the heating rate was 10 ℃ / min, and the whole process was carried out in a nitrogen atmosphere.

[0057] The thermogravimetric analysis (TGA) test method is as follows: A certain amount of sample powder was taken, and the temperature was raised in the range of 30~800 ℃ at a rate of 10 ℃ / min. The whole process was carried out in a nitrogen atmosphere.

[0058] Fourier transform infrared spectra, X-ray diffraction patterns, differential scanning calorimetry (DSC) curves, and thermogravimetric analysis (TGA) curves of β-CD, CD-MOF, EGCG, and EGCG@CD-MOF are shown below. Figure 2 As shown. Among them, Figure 2In the figure, A represents the Fourier transform infrared spectrum of β-CD, CD-MOF, EGCG, and EGCG@CD-MOF; Figure 2 B in the diagram represents the X-ray diffraction pattern of β-CD, CD-MOF, EGCG, and EGCG@CD-MOF. Figure 2 C in the figure represents the differential scanning calorimetry curves of β-CD, CD-MOF, EGCG, and EGCG@CD-MOF. Figure 2 D in the figure represents the thermogravimetric analysis curves of β-CD, CD-MOF, EGCG, and EGCG@CD-MOF.

[0059] Depend on Figure 2 Analysis shows that: Figure 2 As shown in A, the infrared spectra of CD-MOF and CD molecules are similar, indicating that CD-MOF basically maintains the structure of cyclodextrin. + The introduction of EGCG did not change the original structure. The characteristic peaks of EGCG almost disappeared in the EGCG@CD-MOF infrared spectrum, indicating that EGCG has been successfully loaded into the CD-MOF.

[0060] like Figure 2 As shown in B, there are many sharp characteristic diffraction peaks in the spectrum of EGCG. After EGCG is encapsulated in CD-MOF, these characteristic diffraction peaks weaken or disappear, indicating that EGCG was successfully loaded into CD-MOF and exhibited an amorphous state. The EGCG@CD-MOF composite material was successfully synthesized.

[0061] like Figure 2 As shown in C, the DSC spectrum of EGCG shows obvious characteristic absorption peaks: a dehydration peak at around 133 °C, a melting peak at 226 °C, and a thermal decomposition peak at 234 °C. These characteristic peaks shifted or disappeared after EGCG was loaded into CD-MOF, indicating that EGCG was successfully encapsulated in CD-MOF and lost its original crystal morphology.

[0062] like Figure 2 As shown in D, the main thermal degradation temperature of EGCG is between 220 ℃ and 287 ℃, while the thermal degradation temperature in EGCG@CD-MOF is delayed. This may be due to the effective encapsulation of EGCG in CD-MOF. EGCG is protected by the porous structure of CD-MOF, and this loading system improves the thermal stability of EGCG.

[0063] 2. Density Functional Theory (DFT) Calculations of CD-MOF and EGCG The molecular geometry was fully optimized using Gaussian 16 software, employing the B3LYP hybrid functional with a 6-31G(d) basis set. During geometry optimization, Grimme's D3 dispersion correction model was introduced, combined with Becke-Johnson damping functions to accurately describe the dispersion effect and characterize the weak interactions within the system. After geometry optimization, resonant vibrational frequencies were calculated to confirm that the obtained stationary points were true minima on the potential energy surface. Single-point energy calculations used a higher precision level, employing the B3LYP functional and a 6-311G(d,p) basis set. Intermolecular non-covalent interactions were analyzed using Multiwfn software, and the molecular ball-and-stick model was constructed and visualized using GaussView 6.1.16 software. The density functional theory (DFT) optimized structure and the isosurface plot of the independent gradient model (IGMH) for CD-MOF loaded with EGCG are shown below. Figure 3 As shown. Among them, Figure 3 In the diagram, A represents the density functional theory (DFT) optimized structure of CD-MOF loaded with EGCG; Figure 3 B in the figure is the contour plot of the independent gradient model (IGMH) of the CD-MOF load EGCG.

[0064] To elucidate the loading and structural stabilization mechanism of EGCG by CD-MOF at the molecular level, DFT was used to perform full geometric optimization of the composite system of CD-MOF structural unit β-CD and guest molecule EGCG. The results are as follows: Figure 3 As shown in A in the figure. Based on the Independent Gradient Model (IGMH) of Hirshfeld partitions, the non-covalent interactions between host and guest molecules are visualized and characterized, as shown in the figure. Figure 3 As shown in Figure B, the extensive green isosurfaces represent van der Waals forces, while the blue isosurfaces between the O and H atoms of the host and guest molecules represent hydrogen bonding. This indicates that the encapsulation of EGCG by CD-MOF is a result of non-covalent host-guest interactions driven by both hydrogen bonding and van der Waals forces. The multi-site hydrogen bonds formed between the hydroxyl groups of EGCG and the hydroxyl sites of the CD units may provide strong directional forces for host-guest binding, playing a key role in achieving adsorption. Meanwhile, the extensive van der Waals forces between the hydrophobic cavity of CD and EGCG may further fix the molecular conformation of EGCG, enhancing the stability of the system. Simultaneously, the near absence of steric repulsion (red isosurfaces) in the bound regions can be observed from the IMH isosurfaces of the composite system, indicating good spatial adaptation between CD-MOF and EGCG.

[0065] 3. Evaluation of material functional activity The EGCG@CD-MOF complex was prepared according to the method in Example 1 and formulated into aqueous solutions with gradient concentrations of 0.1–1.0 mg / mL. Its antioxidant activity was evaluated using DPPH and ABTS free radical scavenging methods. Simultaneously, the EGCG@CD-MOF complex was prepared according to the methods in Examples 1–3 and Comparative Example 1, and its antibacterial activity against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) was evaluated. The scavenging activities of EGCG@CD-MOF against DPPH and ABTS free radicals, as well as its anti-S. aureus and anti-Escherichia coli activities, are shown in the figure below. Figure 4 As shown. Among them, Figure 4 In the diagram, A represents the scavenging activity of EGCG@CD-MOF against DPPH free radicals. Figure 4 B in the figure represents the scavenging activity of EGCG@CD-MOF against ABTS free radicals. Figure 4 The C in the figure represents the activity of EGCG@CD-MOF against Staphylococcus aureus and Escherichia coli.

[0066] Depend on Figure 4 Analysis showed that the EGCG@CD-MOF complex exhibited a stable and peak scavenging rate of DPPH free radicals within the concentration range of 0.7–0.9 mg / mL, reaching a maximum value (over 90%). The EGCG@CD-MOF complex also demonstrated extremely strong antioxidant activity against ABTS free radicals within the concentration range of 0.2–1.0 mg / mL. Furthermore, it showed a strong inhibitory effect on Staphylococcus aureus within the tested concentration range (0.7–0.9 mg / mL), with an inhibition rate approaching 100%.

[0067] 4. Physical characterization of SA-PVA-EGCG@CD-MOF active composite membrane SA-PVA-EGCG@CD-MOF active composite films were prepared according to the methods in Examples 1-3 and Comparative Example 1. The SA-PVA-EGCG@CD-MOF active composite films were subjected to scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and differential scanning calorimetry (DSC). The methods for FT-IR, XRD, and DSC are as described above. The surface microstructure, cross-sectional microstructure, FT-IR spectrum, X-ray diffraction pattern, and DSC curve of the SA-PVA-EGCG@CD-MOF active composite films are shown below. Figure 5 As shown. Among them, Figure 5 In the figure, A represents the surface microstructure of the SA-PVA-EGCG@CD-MOF active composite film. Figure 5B in the figure represents the cross-sectional microstructure of the SA-PVA-EGCG@CD-MOF active composite membrane. Figure 5 C in the figure represents the Fourier transform infrared spectrum of the SA-PVA-EGCG@CD-MOF active composite film. Figure 5 D in the figure represents the X-ray diffraction pattern of the SA-PVA-EGCG@CD-MOF active composite film. Figure 5 E in the figure represents the differential scanning calorimetry curve of the SA-PVA-EGCG@CD-MOF active composite membrane.

[0068] Depend on Figure 5 Analysis shows that, at different magnifications, the surface of the pure SA-PVA-based film is smooth and clean, without obvious cracks or aggregates. However, no significant differences were observed in the surface of films with different concentrations of EGCG@CD-MOF composite material. This indicates that the EGCG@CD-MOF composite is uniformly dispersed in SA-PVA and does not affect the internal structure or appearance of the film (see...). Figure 5 (A) Meanwhile, the cross-sectional roughness of the composite film also showed no significant difference after the addition of the EGCG@CD-MOF composite material, indicating that it is well distributed in the SA-PVA matrix. The EGCG@CD-MOF composite and SA-PVA still exhibit good miscibility (see A). Figure 5 (B) in the example. Figure 5 As shown in Figure C, the characteristic absorption peaks of SA correspond to the OH stretching vibrations of the hydroxyl groups in its pyranose ring, the asymmetric and symmetric stretching vibrations of the carboxylate ion, and the CO bond stretching vibrations of the sugar ring. The characteristic absorption peaks of PVA correspond to intramolecular / intermolecular OH stretching vibrations, the asymmetric stretching vibrations of the methylene group, the CH bending vibrations, and the CO and CC skeletal stretching vibrations. After SA and PVA are combined, the OH stretching vibration peaks broaden, indicating that they form a stronger and more complex hydrogen bond network through interaction. Both characteristic peaks are retained, confirming successful combination without the formation of new chemical bonds. After introducing the EGCG@CD-MOF composite, the infrared spectrum of the film is basically consistent with that of the SA-PVA film, indicating that it does not change the spatial structure of the SA-PVA-EGCG@CD-MOF active composite film. Figure 5As shown in Figure D, the XRD patterns of the active composite films with different concentrations of EGCG@CD-MOF complex are similar to those of the pure SA-PVA-based film, indicating that the addition of EGCG@CD-MOF complex does not change the crystal structure of the active composite film. Furthermore, no characteristic diffraction peaks of EGCG were observed in the active composite films containing EGCG@CD-MOF complex, suggesting that EGCG, after being encapsulated in CD-MOF and then added to the active composite film, has completely become amorphous, and its bioavailability may be further improved in the active composite film. The DSC curves of the active composite films containing different concentrations of EGCG@CD-MOF complex are shown in Figure D. Figure 5 As shown in E, they are similar to the DSC curves of pure SA-PVA-based films without the addition of EGCG@CD-MOF composite material. Overall, the addition of EGCG@CD-MOF composite material does not affect the crystallinity and thermal stability of SA-PVA-based films.

[0069] 5. Performance evaluation of composite membranes Active composite membranes (SA-PVA-EGCG@CD-MOF) and sodium alginate-polyvinyl alcohol (SA-PVA) based films were prepared according to the methods in Examples 1-3 and Comparative Example 1, respectively. Their water contact angle, water vapor transmission rate, water retention rate, thickness, and mechanical properties were then tested. The water contact angle, water vapor transmission rate, water retention rate, thickness, and tensile properties of the active composite membranes with different EGCG@CD-MOF addition concentrations are shown in the figures below. Figure 6 As shown. Among them, Figure 6 In the figure, A represents the water contact angle of the active composite membrane under different EGCG@CD-MOF addition concentrations; Figure 6 B in the figure represents the water vapor transmission rate of the active composite membrane under different EGCG@CD-MOF addition concentrations; Figure 6 C in the figure represents the water holding capacity of the active composite membrane under different EGCG@CD-MOF addition concentrations; Figure 6 D in the figure represents the thickness of the active composite film at different EGCG@CD-MOF addition concentrations; Figure 6 E in the figure represents the tensile properties of the active composite membrane at different EGCG@CD-MOF addition concentrations.

[0070] Depend on Figure 6 Analysis shows that SA-PVA-based films have excellent hydrophilicity, with a water contact angle of less than 90°. After adding EGCG@CD-MOF, the thickness of the active composite film is maintained between 0.06 and 0.08 mm, the tensile strength increases from 15 MPa of pure SA-PVA-based films to about 20 MPa, the water vapor transmission rate does not change significantly, and the water holding capacity decreases from about 45.8% to 28%~30%.

[0071] 6. Applications of skipjack tuna preservation and deodorization Active composite films (SA-PVA-EGCG@CD-MOF) and sodium alginate-polyvinyl alcohol (SA-PVA) based films were prepared according to the methods described in Examples 1-3 and Comparative Example 1, respectively. Fresh bonito (Katsuwonus pelamis) dorsal muscle (10±0.1 g / piece) was wrapped with the active composite film (SA-PVA-EGCG@CD-MOF) and sodium alginate-polyvinyl alcohol (SA-PVA) based film prepared in Examples 1-3 and Comparative Example 1, respectively. Unwrapped bonito meat served as a blank control group (CK group). The samples were stored at 4 ℃ for 7 days. The color, texture characteristics, pH value, TVB-N content, TBA value, fatty acid composition, microbial community diversity, and volatile flavor compounds of the samples after storage were measured. The effects of different treatment groups on color difference, texture characteristics, pH, TVB-N content, and TBARS content of bonito after 7 days of refrigeration at 4 ℃ are shown in the figure below. Figure 7 As shown. Among them, Figure 7 Figure A shows the effect of different treatment groups on the color difference of skipjack tuna after 7 days of refrigeration at 4 ℃; Figure 7 Figure B in the figure shows the effect of different treatment groups on the textural properties of skipjack tuna after 7 days of refrigeration at 4 ℃. Figure 7 C in the figure represents the effect of different treatment groups on pH of skipjack tuna after 7 days of refrigeration at 4 ℃; Figure 7 D in the figure represents the effect of different treatment groups on the TVB-N content of skipjack tuna after 7 days of refrigeration at 4 ℃; Figure 7 Figure E in the figure represents the effect of different treatment groups on the TBARS content of skipjack tuna after 7 days of refrigeration at 4 ℃. The PCA analysis results of skipjack tuna samples from different treatment groups, as well as the phylum and genus-level microbial community composition, are shown below. Figure 8 As shown. Among them, Figure 8 Figure A in the figure represents the PCA analysis results of skipjack tuna samples from different treatment groups; Figure 8 B in the figure represents the phylum-level microbial community composition of skipjack tuna samples from different treatment groups; Figure 8 In the figure, C represents the genus-level microbial community composition of skipjack tuna samples from different treatment groups.

[0072] Depend on Figure 7Analysis showed that the L* value (brightness) of the EGCG@CD-MOF complex-treated group was significantly higher than that of the blank control group, the a* value (redness) was higher than that of the blank control and the pure membrane (i.e., the SA-PVA-based film in Comparative Example 1) treatment group, the b* value (yellowness) was lower than that of the blank control group, and the W value (whiteness) was significantly higher than that of other treatment groups. This indicates that the active composite membrane can effectively inhibit myoglobin oxidation and lipid oxidation-induced yellowing. The skipjack tuna in the EGCG@CD-MOF complex-treated group showed significantly improved hardness and elasticity, increased cohesion and chewiness, indicating that the active composite membrane (SA-PVA-EGCG@CD-MOF) can protect the integrity of myofibril proteins and delay meat quality deterioration. The TVB-N value of the pure SA-PVA-based film treatment group was approximately 31 mg / 100g, exceeding the upper limit of 30 mg / 100g for food safety. The TVB-N value of the EGCG@CD-MOF complex (0.9 mg / mL) treatment group (i.e., Example 3) decreased to approximately 25 mg / 100g, the pH value decreased from approximately 6.5 in the blank control to approximately 6.1, and the TBA value remained at 0.6~0.7 mg MDA / kg.

[0073] Depend on Figure 8 Analysis showed that 16S rRNA sequencing analysis indicated that the relative abundance of Pseudomonas in the EGCG@CD-MOF complex-treated group decreased significantly, while the abundance of non-dominant genera (such as Ralstonia, Acinetobacter, and Brochothrix) increased, and the balance of the microbial community structure was significantly optimized.

[0074] The test method for fatty acids is as follows: The fatty acid content in skipjack tuna samples from different treatment groups was determined using a hydrolysis-extraction combined with gas chromatography. After hydrolysis, the fat was extracted using a mixed solvent of diethyl ether and petroleum ether. The extracted fat was then saponified and methylated under alkaline conditions to generate the corresponding fatty acid methyl esters. The methylation process was as follows: 20 mg of the extracted fat was accurately weighed and placed in a 50 mL centrifuge tube. 4 mL of 0.5% sodium hydroxide-methanol solution was added, and the mixture was heated in a 45 °C water bath for 20 min for saponification. Subsequently, 4 mL of 14% boron trifluoride-methanol solution was added, and the mixture was heated in a 45 °C water bath for another 20 min to complete the methylation reaction. After cooling the reaction solution to room temperature, 3 mL of chromatographically pure n-hexane was added for extraction for 2 min, followed by the addition of 10 mL of saturated sodium chloride solution. After centrifugation, the upper n-hexane phase was collected as the analyte.

[0075] Analysis was performed using a gas chromatograph (Shimadzu GC-2014) equipped with a SIGMA SP-2560 capillary column (100 m × 0.25 mm × 0.2 μm). Chromatographic conditions were set as follows: injection port temperature 250 ℃, detector: FID, temperature 260 ℃; carrier gas: nitrogen, flow rate 1.4 mL / min; hydrogen flow rate 40 mL / min, air flow rate 400 mL / min; split ratio 20:1, injection volume 1 μL. A gradient temperature program was used in the column oven: initial temperature 140 ℃ held for 5 min, then increased to 240 ℃ at a rate of 4 ℃ / min and held for 20 min. Quantification was performed using the external standard method. A standard curve was plotted using a mixture of 37 fatty acid methyl ester standards. The content of fatty acid methyl esters in the sample was calculated based on the peak area, and the final fatty acid content in the sample was converted using conversion factors. The fatty acid content of skipjack tuna samples from different treatment groups after storage at 4 ℃ for 7 days is shown in Table 1 below.

[0076] Table 1: .

[0077] Analysis of the data in Table 1 shows that, compared with the blank bonito treatment group without film coating (CK group) and the treatment group using only SA-PVA-based film, the total fatty acid content of the bonito treatment group loaded with EGCG@CD-MOF complex material was significantly increased, and the retention rate of total fatty acids also increased with the increase of EGCG@CD-MOF complex concentration. This indicates that EGCG has a strong antioxidant effect on bonito and may be slowly released in CD-MOF, maintaining a high concentration of antioxidant microenvironment on the surface of bonito meat during the 7-day storage period, thereby effectively blocking lipid oxidation. The EPA content of the bonito treatment group loaded with EGCG@CD-MOF complex material increased from 7.7 mg / 100g in the blank control to 10.03~13.27 mg / 100g, and the DHA content increased from 65.03 mg / 100g to 77.10~114.59 mg / 100g.

[0078] The testing methods for volatile flavor compounds are as follows: Accurately weigh 600±12 mg of ground skipjack tuna samples from different treatment groups and place them in 20 mL headspace vials. Add 1 mL of saturated sodium chloride solution containing the internal standard (the internal standard is 10 mg / L 2-octanol aqueous solution, and the volume ratio of saturated sodium chloride solution to internal standard stock solution is 100:1). Simultaneously prepare a mixed standard sample of C9-C23 n-alkanes for subsequent retention index calibration. Gas chromatography-mass spectrometry non-target volatile metabolomics analysis was performed using an Agilent 8890B gas chromatograph coupled with a 5977B mass spectrometer. A DB-Wax column (30 m×250 μm×0.25 μm) was used for headspace solid-phase microextraction (SPE) using a Smart SPME Fiber DVB / CWR / PDMS fiber head. The conditions were: incubation temperature 60 ℃, preheating for 15 min, incubation and extraction for 30 min, and desorption for 4 min. In splitless injection mode, helium was used as the carrier gas, with a septum purge flow rate of 3 mL / min at the sample inlet and a column flow rate of 1 mL / min. The column temperature program was: initial 40 °C, held for 4 min, then ramped up to 245 °C at 5 °C / min and held for 5 min. The temperatures for the sample inlet, transfer line, ion source, and quadrupole were 250 °C, 250 °C, 230 °C, and 150 °C, respectively. Electron impact ionization was performed at an energy of 70 eV. Mass spectrometry data were acquired in full scan mode, with an m / z range of 20–400 and a solvent delay of 2.37 min. Data processing was performed using LECO's Chroma TOF 4.3X software, including peak extraction, baseline correction, peak alignment, deconvolution, peak identification, peak area integration, and mass spectrometry matching. Metabolite identification was performed using the NIST database, and retention indices were calculated based on the detection results of a mixed standard of C9-C23 n-alkanes to assist in the calibration of the qualitative results. The statistical analysis of the types and quantities of volatile substances and the scatter plot of ROAV values ​​in skipjack tuna from different treatment groups are shown below. Figure 9 As shown. Among them, Figure 9 In the figure, A represents a statistical chart of the types and quantities of volatile substances in skipjack tuna from different treatment groups; Figure 9 B in the figure represents the scatter plot of ROAV values ​​in skipjack tuna from different treatment groups. The volatile matter content and ROAV values ​​of different treatment groups are shown in Table 2 below.

[0079] Table 2: .

[0080] Depend on Figure 9 Analysis revealed that after 7 days of refrigeration, 71 volatile substances were identified from different treatment groups using GC-MS technology. These substances covered ten major categories, including alcohols, aldehydes, ketones, acids, and esters. Alcohols and aldehydes were the most numerous, and they are the main substances produced by lipid oxidation and microbial metabolism during the refrigeration of aquatic products (see...). Figure 9(A) The flavor contribution of 71 volatile substances was quantified using the ROAV method. The scatter plot of ROAV values ​​for the five treatment groups is shown in Figure 1. Figure 9 B in the figure visually presents the flavor contribution distribution characteristics of volatile substances in refrigerated skipjack tuna. Generally, substances with a ROAV value greater than 1 are considered key flavor contributors, which determine the main flavor characteristics of the sample.

[0081] Analysis of the data in Table 2 shows that hexanal was the most abundant and had the highest ROAV value among the six aldehydes, indicating that hexanal is the most critical odor-causing substance in the preservation of skipjack tuna. In the blank control group (CK group), the hexanal content was 0.1042, which was similar to that in the pure SA-PVA film-coated group (0.0965). However, with the addition of the EGCG@CD-MOF complex, the hexanal content decreased, with the 0.9 mg / mL group (Example 3) showing a decrease to 0.0775, a 25.62% decrease compared to the CK group. The trends of heptanal and octanal were similar to those of hexanal, while the trend of nonanal differed, with smaller overall fluctuations. This suggests that EGCG, after being released from CD-MOF, may reduce the characteristic fishy odor of skipjack tuna by inhibiting lipid oxidation and reducing the generation of secondary volatile substances such as aldehydes at the source.

[0082] Among alcohols, 1-octen-3-ol had a ROAV value as high as 100 in all treatment groups, making it a key substance determining the main flavor of chilled skipjack tuna. In the blank control group (CK group), the 1-octen-3-ol content was 0.0735, which decreased to 0.0617 in the pure SA-PVA-based film-coated group, a decrease of 16.05% compared to the CK group. The active composite film group loaded with the EGCG@CD-MOF complex further reduced its content, with an overall decrease of 26%–27% compared to the CK group. The decrease in 1-octen-3-ol content may be due to EGCG inhibiting the oxidation of ω-3 series polyunsaturated fatty acids such as linolenic acid.

[0083] The above description is merely a detailed explanation of preferred embodiments and principles of the present invention. For those skilled in the art, there may be changes in specific implementation methods based on the ideas provided by the present invention, and these changes should also be considered within the scope of protection of the present invention.

Claims

1. A loaded EGCG@CD-MOF active composite membrane for preserving and removing the odor from aquatic products, characterized in that, The active composite membrane comprises sodium alginate, polyvinyl alcohol, and EGCG@CD-MOF complex; the EGCG@CD-MOF complex is prepared by loading epigallocatechin gallate into a β-cyclodextrin-based metal-organic framework.

2. The EGCG@CD-MOF loaded active composite membrane for preserving and removing odor from aquatic products according to claim 1, characterized in that, The mass ratio of sodium alginate to polyvinyl alcohol is 1:0.5~2.

3. The EGCG@CD-MOF loaded active composite membrane for preserving and removing odor from aquatic products according to claim 1, characterized in that, The active composite membrane also contains glycerol.

4. A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing odor from aquatic products as described in any one of claims 1 to 3, characterized in that, Includes the following steps: S1: β-Cyclodextrin was dissolved in water with a strong base and crystallized by methanol vapor diffusion to obtain β-CD-MOF crystals; S2: Epigallocatechin gallate ester and the β-CD-MOF crystals obtained in step S1 are mixed in an organic solvent, and after stirring in the dark, centrifugation, washing and drying, the EGCG@CD-MOF complex is obtained. S3: Dissolve sodium alginate and polyvinyl alcohol in water, heat and stir until completely dissolved, and cool to obtain sodium alginate-polyvinyl alcohol film-forming solution; S4: Add the EGCG@CD-MOF complex and glycerol obtained in step S2 to the sodium alginate-polyvinyl alcohol film-forming solution obtained in step S3, stir evenly, degas, cast into a film by casting method, and dry to obtain the active composite film.

5. A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing the odor of aquatic products according to claim 4, characterized in that, The mass ratio of epigallocatechin gallate to β-CD-MOF crystals added in step S2 is 1:0.5~3.

6. The method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing odor from aquatic products according to claim 4, characterized in that, The ratio of the EGCG@CD-MOF complex added in step S4 to the sodium alginate-polyvinyl alcohol film-forming solution is 0.3~2.0:1 mg / mL.

7. A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing odor from aquatic products according to claim 4, characterized in that, The glycerol added in step S4 accounts for 0.5~2.0% of the volume of the sodium alginate-polyvinyl alcohol film-forming solution.

8. A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing the odor of aquatic products according to claim 4, characterized in that, In step S1, the diffusion temperature of methanol vapor diffusion process is 40~60 ℃ and the diffusion time is 8~24 h; the crystallization temperature is 20~30 ℃ and the crystallization time is 12~48 h.

9. A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing the odor of aquatic products according to claim 4, characterized in that, The organic solvent in step S2 is methanol; the stirring time in the dark is 2-8 h; the stirring time in the dark is 5 h.

10. A method for preparing an EGCG@CD-MOF-loaded active composite membrane for preserving and removing the odor of aquatic products according to claim 4, characterized in that, In step S4, ultrasonic treatment is used for degassing for 10-60 min, the drying temperature is 25-40 ℃, and the drying time is 12-48 h.